Instagram Social Media as A Means of Information on Tribal Activities, National Unity Agency and Politics of North Jakarta Administrative - Fatika, Amelia Nur; Fauziah, Fauziah (Devotion : Journal of Research and Community Service, 2023)
Technological developments are increasingly facilitating communication, especially the dissemination of convenience to the public regarding the dissemination of information. Now everyone can receive the latest information or the latest news just by accessing the internet network, for example online media or commonly called social media. Convenience like this can help the government, especially in conveying the latest news or information regarding government policies. The development of information technology brings changes to society, one of which is the existence of social media. Social media is categorized into different groups with different purposes, ranging from young people, adults, business people and government agencies. Government agencies are beginning to recognize the vital role of social media. There are many government social media websites that offer a variety of content, including information about government agencies. Present quality information to attract attention. Therefore, the purpose of this study is to explain how Instagram is managed as a communication tool in the North Jakarta Political Unity Authority tribal administrative district. The research methods used are descriptive and qualitative. Data collection techniques were performed through observations, interviews and documentation. Analyzing research material, presenting information, and drawing conclusions through data reduction. Findings indicate that Instagram is being used to disseminate information about Kesvanpol's activities. The phases of Instagram management include the recording or video phase, the content editing phase, and the publishing phase.